More Than Movement: Exploring Motor Simulation, Creativity, and Function in Co-developed Dance for Parkinson’s - Bek, Judith; Arakaki, Aline I.; Derbyshire-Fox, Fleur; Ganapathy, Gayathri; Sullivan, Matthew; Poliakoff, Ellen (Frontiers in Psychology, 2022)
Dance is an enjoyable, non-therapy-focused activity that may provide a range of benefits for people with Parkinson’s. The internal simulation of movement through observation, imitation, and imagery, is intrinsic to dance and may contribute to functional improvements for people with Parkinson’s. This project explored the feasibility and potential benefits of a dance program designed by a collaborative team of dance artists, researchers, physiotherapists, and people living with Parkinson’s. The program incorporated motor simulation through observation, imitation and imagery of movement, supported by creative themes, expression, and music. A 6-week dance program was piloted with 10 people with Parkinson’s. A focus group following the trial (N=8) provided insights into the use of imagery, observation and imitation within dance, and the link between creativity and functional outcomes, as well as indicating multidimensional benefits of dance as reported in previous studies. Exploratory outcome measures also suggested potential effects on motor simulation, functional dexterity, and quality of life. The present study demonstrates the feasibility of a co-developed dance program for Parkinson’s and indicates how creative elements of dance may support functional outcomes. Future research should examine the role of motor simulation processes in dance for Parkinson’s, including the potential to develop transferable cognitive-motor skills. This study also highlights the value of collaborative partnerships in designing dance for health programs, which may optimise beneficial effects by using creative approaches to incorporate evidence-based elements, with guidance from individuals with lived experience to ensure the relevance to their goals.